Rancang Bangun Website E-Learning dengan Pemodelan UML - Zulkifli Zulkifli (INTECOMS: Journal of Information Technology and Computer Science, 2018)
The learning system that takes place is only done in the classroom and there is no online learning media that uses information technology to support learning. This e-learning application is network based, which is an international standard application, a learning application that is supported by information technology. This study aims to determine the e-learning website design with UML modeling. Searching for information and learning that is only done face-to-face in the classroom is very clear can hamper the learning process with limited time. In supporting teaching and learning activities by utilizing information technology, it is necessary to make a web-based E-Learning application using PHP and MySQL database. Keywords: E-learning, MySQL, PHP, Web